Photoplastic Effect in Narrow-Gap Mercury Chalcogenide Crystals - Koman, B.P.; Balitskii, O.O.; Leonov, D.S. (Металлофизика и новейшие технологии, 2018)
The paper elucidates the peculiarities of photoplasticization effect (PPE) occurring in narrow-gap crystals of mercury chalcogenides illuminated by white light during the process of uniaxial deformation. As found, the irradiation has an influence on the plastic deformation in narrow-gap CdxHg₁₋xTe crystals. Negative photoplasticization effect (NPPE) described here is concerned with reducing of plastic stress fluidity under white-light irradiation during plastic deformation of crystals at a constant rate. As found, in contrary to wide-bandgap crystals of the II–VI groups exhibiting positive PPE, NPPE observed in CdxHg₁₋xTe occurs without internal photoeffect. A model explaining the nature of NPPE relies on a decreasing of positive charge in a native oxide layer at the surface of crystal. Charge decreasing reduces potential barrier for exiting on surface of dislocations generated by near-surface sources during dynamical loading. As a result, the level of fluidity stress in the deformed crystal is reduced.